The Role of the Unity of Knowledge and Example in the Improvement of Personal Moral Qualities (Eurasian Research Bulletin, 2022)
This article describes the role of the unity of knowledge and example in the improvement of moral qualities of a person. Also, in the matter of knowledge and wisdom, the importance of the teachings of the enlightened people to the spiritual maturity of a person is analyzed.